EFEKTIVITAS PEMBERIAN AIR REBUSAN CENGKEH DAN AIR REBUSAN JAHE TERHADAP PENURUNAN NYERI ASAM URAT PADA LANSIA DI PANTI SOSIAL LANJUT USIA HARAPAN KITA PALEMBANG TAHUN 2023 - Royani, Evi; Siska, Fera; Nurza Maya Anjla (LPPM STIKes Mitra Adiguna, 2024)
Gout or gout is a joint disease caused by high levels of uric acid in the blood. The buildup of uric acid that makes the joints feel sore, painful, and even inflamed. According to the World Health Organization (WHO), the incidence of gout in the elderly has increased by 355 million people. Fetermine the effectiveness of clove cooking water and ginger boiled water on reducing gout pain in the elderly in the elderly social institution of our hope Palembang in 2023. The method used is pre-experimental research (Pre Exsperimental designs) with One Group Pretest Post approach. The sample used was 30 respondents with a sampling technique using purposive sampling. Respondents were divided into 2 intervention groups, namely 15 respondents of the clove group and 15 respondents of the ginger group. Measurement of pain scale using Numeric Rating Scale (NRS) and observation sheet. Based on non-parametric statistical tests (wilcoxon) obtained the calculated value of giving air clove decoction of ? = 0.003 and giving ginger boiled water of ? = 0.005 smaller than the significant level of 5% or (p value = 0.000 < 0.05). There is a significant difference based on the average acid pain in the elderly before giving clove cooking water and ginger cooking water is 2.80 and the average gout pain in the elderly after giving clove cooking water is 2.20 and ginger cooking water is 2.27. There is a significant difference in giving clove cooking water and ginger cooking water to reduce gout pain. Giving clove cooking water is more effective to reduce gout pain because cloves have more anti-inflammatory and analgesic compounds than ginger.